Persistent Postural Perceptual Dizziness Induced by Caloric Testing: A Case Report - Workman, Brady S.; Desmond, Alan L. (Journal of the American Academy of Audiology, 2022)
Background The condition of persistent postural perceptual dizziness (PPPD) is a common chronic vestibular disorder that is thought to be due to a central vestibular maladaptation. The condition is frequently encountered in those with a history of migraine, anxiety, or panic attacks. Many cases of PPPD are preceded by vestibular disorders, with vestibular migraine thought to precede at least 20% of cases.Purpose Those with a history of migraine have been shown to have difficulties with sensory integration, habituation, and intolerance to stimuli. This often leads to discomfort associated with some vestibular test procedures, specifically caloric irrigations. At this time there has been little investigation into any prolonged symptoms associated with undergoing vestibular test procedures in this population.Conclusions We pose a case report of a patient with a history of migraine that developed new-onset PPPD following caloric irrigations.
Keywords: persistent postural perceptual dizziness; migraine; vestibular migraine; dizziness